Forecast increase in invasive rabbit spread into ecosystems of an oceanic island (Tenerife) under climate change. Issue 1 (9th September 2020) - Bello‐Rodríguez, Víctor; Mateo, Rubén G.; Pellissier, Loïc; Cubas, Jonay; Cooke, Brian; González‐Mancebo, Juana María
Abstract: The European rabbit ( Oryctolagus cuniculus ) is a pest and a conservation problem on many islands, where its heavy grazing pressure threatens many endemic plants with extinction. Previous studies in its native and introduced range have highlighted the high spatial variability of rabbit abundance at local and landscape scales, depending on many factors such as the existence of different habitats. Modeling of the species can be useful to better understand spatial patterns and to prioritize actions, especially in those regions in which rabbits have become invasive. Here, we investigate the distribution of the European rabbit in Tenerife (Canary Islands, Spain), where the species was introduced during the 15th century and has subsequently changed vegetation composition. Added to the direct effects of rabbits on vegetation, climate change could also have implications for rabbit populations, especially in the alpine ecosystem. To evaluate that, we estimated rabbit abundance in 216 plots randomly distributed on Tenerife island (61 in the alpine ecosystem), modeled the potential current spatial abundance of the species and considered how it might vary under different climate change scenarios. We associated rabbit abundance to a wide selection of abiotic, biotic, and human variables expected to influence rabbit abundance on the island. We found a positive correlation between rabbit abundance and temperature and a negative correlation in the case of precipitation. Hence, according to the models' projections, climate change is expected to enhance rabbit populations in the future. Current higher densities were related to land disturbance and open areas, and a remarkable increase is expected to occur in the alpine ecosystem. Overall, we consider that this study provides valuable information for land managers in the Canary archipelago as it reveals how global warming could indirectly exacerbate the conservation problems of the endemic flora in oceanic islands.